Accurate in situ oxygen isotopic analysis at high resolution by secondary ion mass spectrometry shows the potential of aragonite as a reference material. Issue 7 (22nd May 2021) - He, Miaohong; Chen, Tianyu; Liu, Xi; Yang, Ya-Nan; Xia, Xiaoping; Yang, Qing; He, Pengli; Di, Jian; Zhang, Yanqiang; Wei, Gangjian
Abstract : Matrix effect in SIMS aragonite oxygen isotopic analysis. Abstract : Oxygen isotopic analysis of aragonite by secondary ion mass spectrometry (SIMS) is of significance to reveal the high spatial resolution information correlated with microstructure which could not be achieved by conventional methods. Appropriate reference materials to calibrate instrumental mass fractionation of SIMS are vital to acquire accurate values. However, the scarcity of standards (as far as we know, there were just two in-house laboratory-based potential reference materials reported) limits the development of this field. Herein, an inorganically precipitated aragonite vein sample (VS001/1-A) being evaluated through several hundred SIMS oxygen isotopic analyses was ascertained to have homogeneous oxygen isotopic composition with an external reproducibility of 0.3‰ (1 σ ) and to be a potential SIMS reference material. The instrumental bias evident in the series of aragonites, decreased by ∼3.4‰ with decreasing aragonite Ca content. Corals, as biogenic carbonates, were used as examples for evaluating the application of the in situ SIMS analysis method, and processes involved in "vital effects" are described. The development of in situ oxygen isotopic microanalysis of aragonite is significant for the application of revealing possible biocarbonate mineralization mechanisms.